Factors associated with adherence towards different vaccines of childhood immunization of under five children among mothers attending Klinik Kesihatan Seremban - Zainal Abidin, Zamzaireen (2017)
Introduction: Immunization schedule varies among each country based on situations and diseases. Adherence namely completeness and timeliness towards the schedule is the basis of children protection as seroconversion is age-dependent. Hence, even if immunization coverage is persistently high, as of late, vaccine preventable diseases are on the rise.